Uncoupling DISC1 × D2R Protein-Protein Interactions Facilitates Latent Inhibition in Disc1-L100P Animal Model of Schizophrenia and Enhances Synaptic Plasticity via D2 Receptors - Lipina, Tatiana V.; Beregovoy, Nikolay A.; Tkachenko, Alina A.; Petrova, Ekaterina S.; Starostina, Marina V.; Zhou, Qiang; Li, Shupeng (Frontiers in Synaptic Neuroscience, 2018)
Both Disrupted-In-Schizophrenia-1 (DISC1) and dopamine receptors D2R have significant contributions to the pathogenesis of schizophrenia. Our previous study demonstrated that DISC1 binds to D2R and such protein-protein interaction is enhanced in patients with schizophrenia and Disc1-L100P mouse model of schizophrenia (Su et al., 2014). By uncoupling DISC1xD2R interaction (TAT-D2pep), the synthesized TAT-peptide elicited antipsychotic-like effects in pharmacological and genetic animal models, without motor side effects as tardive dyskinesia commonly seen with typical antipsychotic drugs (APD), indicating that the potential of TAT-D2pep of becoming a new APD. Therefore, in the current study, we further explored the APD-associated capacities of TAT-D2pep. We found that TAT-D2pep corrected the disrupted latent inhibition, as a hallmark of schizophrenia associated endophenotype, in Disc1-L100P mutant mice - a genetic model of schizophrenia, supporting further APD’ capacity of TAT-D2pep. Moreover, we found that TAT-D2pep elicited nootropic effects in C57BL/6NCrl inbred mice, suggesting that TAT-D2pep acts as a cognitive enhancer, a desirable feature of APDs of the new generation. Namely, TAT-D2pep improved working memory in T-maze, and cognitive flexibility assessed by the latent inhibition paradigm, in C57BL/6N mice. Next, we assessed the impact of TAT-D2pep on hippocampal long-term plasticity (LTP) under basal conditions and upon stimulation of D2 receptors using quinpirole. We found comparable effects of TAT-D2pep and its control TAT-D2pep-scrambled peptide (TAT-D2pep-sc) under basal conditions. However, under stimulation of D2R by quinpirole, LTP was enhanced in hippocampal slices incubated with TAT-D2pep, supporting the notion that TAT-D2pep acts in a dopamine-dependent manner and acts as synaptic enhancer. Overall, our experiments demonstrated implication of DISC1xD2R protein-protein interactions into mechanisms of cognitive and synaptic plasticity, which help to further understand molecular-cellular mechanisms of APD of the next generation.